Evaluating Innovation Efficiency in EU Countries: the DEA Approach (Marketing i Menedžment Innovacij)
Innovation, science and technology, which are among the most important tools for achieving economic growth, prosperity and competitiveness in the local and global business environments, are increasingly gaining attention. Thus, improving the level of innovation efficiency of countries should be one of the EU priorities. The aim of this paper is to analyse the development of the innovation efficiency of EU member states and to assess the use of resources entering their national innovation systems. To determine the efficiency of the EU countries, basic output-oriented DEA models were applied. The data were processed from databases of the World Bank. First, the development and comparative analysis of input variables (government expenditure on education as a percentage of gross domestic product, research & development expenditure as a percentage of gross domestic product, researchers in research & development per million people) and output variables (patent applications, high-technology exports as a percentage of manufactured exports and scientific and technical journal articles) was performed. The level of efficiency of individual EU countries was subsequently quantified via DEA Solver (LV 8.0) software. Based on the scaling method, 5 groups of countries with similar levels of efficiency were identified and presented in the cartogram (efficient countries, above-average efficient countries, average efficient countries, below-average efficient countries, and inefficient countries). Over the period analysed, a total of 6 countries were identified as efficient – France, Germany, Ireland, Italy, Malta, Romania (and the United Kingdom in 2018–2019). Countries such as Sweden, Denmark, Belgium, Finland and Austria recorded the highest values of the selected inputs, but the efficiency score showed average to below-average results. The findings of this study demonstrated that many of the top-ranked nations in global innovation rankings are misusing and underutilizing the resources that enter their national innovation systems. Makers of policies and strategic plans for the innovation efficiency of EU countries will thus have the opportunity to incorporate the results of the study into real proposals and solutions.